Tolak Ukur Kebijakan Pembagian Dividen pada Perusahaan Go-Public - Wirawan, Rendra (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2019)
Dividends are profit rights granted to shareholders sourced from the ability of the issuer to make a net profit from operating activities. Dividends are usually distributed at the end of the accounting year which is decided from the results of the GMS (General Meeting of Shareholders). The ratio of the dividend payout rate is called the DPR (dividend payout ratio). This ratio shows the percentage of profits paid by companies in the form of dividends with the total profit available to shareholders. The purpose of this research is to find out and analyze the company’s benchmarks in determining dividend distribution policy on companies going public. There are several ratios that can influence companies in determining dividend distribution policies. The ratio is the ratio of profitability which is proxied by the value of ROA, leverage is proxied by the value of Current Ratio and the value of the company which is proxied by the value of PER (Price Earning Ratio). This research is a type of quantitative research using secondary data that is the financial statements of go-public companies in banking companies in 2015-2017. Targeted outputs are international journals, proceedings in local scientific meetings and IPR. TKT is at level 2: the basic assumptions and laws that will be used in technology reaches 80%, the study of literature on the basic principles of technology reaches 80% and the formulation of research hypotheses reaches 80%.